(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract: The integration of artificial intelligence (AI) with wearable technology marks a significant advancement in continuous health and nutritional monitoring. This paper explores how AI enhances wearable devices, enabling them to provide real-time, personalized insights into nutritional intake and health metrics. By combining sophisticated AI algorithms with data from various sensors, wearable technology can continuously track and analyze physiological parameters such as heart rate, activity levels, and metabolic responses. This integration offers several benefits, including improved accuracy in dietary assessments, personalized health recommendations, and proactive health management. AI-driven wearables automate the monitoring process, reducing reliance on manual input and enhancing the reliability of health and nutritional data. Challenges such as data privacy, algorithm accuracy, and data integration need to be addressed to maximize the potential of these technologies. Future research should focus on refining AI algorithms, improving sensor technologies, and ensuring robust data security measures. Overall, the synergy between AI and wearable technology holds promise for transforming personal health management, offering new opportunities for optimizing health and well-being through continuous, personalized monitoring.